2022
DOI: 10.1021/jacs.2c05792
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Morphology and Elemental Distribution of Cu-In Nanocrystals via Galvanic Replacement

Abstract: The compositional and structural diversity of bimetallic nanocrystals (NCs) provides a superior tunability of their physico-chemical properties, making them attractive for a variety of applications, including sensing and catalysis. Nevertheless, the manipulation of the properties-determining features of bimetallic NCs still remains a challenge, especially when moving away from noble metals. In this work, we explore the galvanic replacement reaction (GRR) of In NCs and a copper molecular precursor to obtain Cu-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…Galvanic replacement reaction (GRR) is an electrochemical process widely utilized in various aspects of our daily lives, such as voltaic cells, metal corrosion and anticorrosion, and electroless metal deposition . Over the past two decades, the GRR has attracted considerable attention in the field of nanoscience and nanotechnology, owing to its ability to engineer metal nanostructures. Specifically, the GRR involves the interaction between nanoparticles of a sacrificial template metal and ions of a noble metal, resulting in the formation of bimetallic hollow nanostructures (Figure a–c). Thus far, a variety of bimetallic nanostructures with tunable size, morphology, and composition have been achieved through GRR, which finds widespread applications in various fields, such as catalysis and energy storage . In a typical GRR synthesis process, the template materials, ionic species, stoichiometry, and temperature , need to be considered carefully.…”
Section: Introductionmentioning
confidence: 99%
“…Galvanic replacement reaction (GRR) is an electrochemical process widely utilized in various aspects of our daily lives, such as voltaic cells, metal corrosion and anticorrosion, and electroless metal deposition . Over the past two decades, the GRR has attracted considerable attention in the field of nanoscience and nanotechnology, owing to its ability to engineer metal nanostructures. Specifically, the GRR involves the interaction between nanoparticles of a sacrificial template metal and ions of a noble metal, resulting in the formation of bimetallic hollow nanostructures (Figure a–c). Thus far, a variety of bimetallic nanostructures with tunable size, morphology, and composition have been achieved through GRR, which finds widespread applications in various fields, such as catalysis and energy storage . In a typical GRR synthesis process, the template materials, ionic species, stoichiometry, and temperature , need to be considered carefully.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, a Pd overlayer on the surface of Au NPs was demonstrated to be more resilient to dissolution than pure Pd NPs because of the Au–Pd bond being stronger compared to the Pd–Pd bond . Cu-based alloyed NPs are currently investigated as CO 2 RR catalysts; however, these studies mostly focus on tuning the selectivity rather than aiming at developing guidelines toward increasing the performance stability of the Cu NPs. , Based on the current knowledge regarding the reconstruction of Cu in CO 2 RR and inspired by the studies on oxygen electrocatalysis, we hypothesize that the combination of Cu with an element M that possesses a higher oxophilicity and lower electronegativity than Cu should reduce the tendency of Cu to oxidize at ocp and form heteroatomic Cu–M bonds with higher dissociation energies than Cu–Cu, which should further hamper Cu dissolution and thus improve the performance stability of Cu NPs during CO 2 RR.…”
Section: Introductionmentioning
confidence: 99%
“…Single-atom catalysts with well-defined and atomically dispersed active sites provide an ideal prototype to explore the exact structure of the catalytic site under reaction conditions, which should be beneficial to achieve a comprehensive understanding on the metastable state of Cu-based catalysts and the closely related performance toward the target product. Recently, various studies have demonstrated that atomic doping of heteroatoms (e.g., Sn, In, Bi, etc.) into Cu matrix materials displayed remarkably high selectivity for electrochemical CO 2 reduction to CO or HCOOH due to the stabilized Cu δ+ species that modified the binding energy of intermediates. , , However, the fundamental role of single metal atoms in stabilizing the catalytic sites with a desired electronic structure is still unclear.…”
Section: Introductionmentioning
confidence: 99%